PENGAJARAN SASTRA DENGAN TEORI NEW HISTORICISM - I Wayan Artika (Universitas Pendidikan Ganesha, 2015)
Althought literature study developed rapidly but literature teaching to the full use it advancement not yet. Hence, literature teaching in schools necessary use recent literature study/critic. In a general way teachers opinion said that “on behalf of teaching seriously, so by means of “the bad way” was sufficient for students to answer the objective test. As the world goes, literature teaching is structurally. According to teachers, literature is “a deformity good” because most parts of literature were dominate by imagination. This short paper would like to contribute teachers within literature teaching, as the thing which “challenge” benefited New Historicism and intertextuality approach.Key words: literature teaching, New Historicism, intertextuality approach, fact and fiction